Prosedur Pelaksanaan Pajak Penghasilan Pasal 21 Terkait Natura Pada PT Sinergi Gula Nusantara - Risa Bonani Prastika; R. Yuniardi Rusdianto (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
PT Sinergi Gula Nusantara, which is a subsidiary of Holding Perkebunan Nusantara (Persero), is a national sugar industry and overseas 36 sugar factories throughout Indonesia. Income Tax 21 policy on natura or enjoyment obtained in tax implementation. This research is written using descriptive method of analysing the results directly to the company during the internship. As for natura or enjoyment obtained by employees in the form of Office Clothing, K3 facilities, Health COB, Extra Voiding, Sports Activities, Icip-Icip Sugar, PG Service House, Service Vehicles for certain Positions and Pension Contributions by the Company.